Breakdown characteristics of CF4 and CF4/N2 hybrid gas in refrigeration temperature range - Hou, Meng-xi; Li, Wei-guo; Yuan, Chuang-ye; Yang, Yi-xin; Ouyang, Jie (Journal of Central South University, 2017)
Common insulation gas cannot normally work in refrigeration temperature range (153−243 K), especially in extremely cold regions. To solve this problem, this essay uses cubic equation combined with two-parameter model in theorem of corresponding states to estimate dew-point of hybrid gas. The influence of temperature on mixing ratio is studied by using van der Waals equation. The result shows that the mixing ratio is stable during temperature-fall period. Insulation property of CF 4 and CF 4 /N 2 in refrigeration temperature range is studied through self-designed low-temperature test system. The result shows when the density of hybrid gas is invariable, temperature changing has less influence on breakdown voltage, and when the mixing ratio is 20%, CF 4 /N 2 is the greatest potential hybrid gas.